Structural Complexity and Plasticity of Signaling Regulation at the Melanocortin-4 Receptor - Gunnar Kleinau (International Journal of Molecular Sciences, 2020)
The melanocortin-4 receptor (MC4R) is a class A G protein-coupled receptor (GPCR), essential for regulation of appetite and metabolism. Pathogenic inactivating MC4R mutations are the most frequent cause of monogenic obesity, a growing medical and socioeconomic problem worldwide. The MC4R mediates either ligand-independent or ligand-dependent signaling. Agonists such as α-melanocyte-stimulating hormone (α-MSH) induce anorexigenic effects, in contrast to the endogenous inverse agonist agouti-related peptide (AgRP), which causes orexigenic effects by suppressing high basal signaling activity. Agonist action triggers the binding of different subtypes of G proteins and arrestins, leading to concomitant induction of diverse intracellular signaling cascades. An increasing number of experimental studies have unraveled molecular properties and mechanisms of MC4R signal transduction related to physiological and pathophysiological aspects. In addition, the MC4R crystal structure was recently determined at 2.75 Å resolution in an inactive state bound with a peptide antagonist. Underpinned by structural homology models of MC4R complexes simulating a presumably active-state conformation compared to the structure of the inactive state, we here briefly summarize the current understanding and key players involved in the MC4R switching process between different activity states. Finally, these perspectives highlight the complexity and plasticity in MC4R signaling regulation and identify gaps in our current knowledge.